Recommendations Improving the Linkage between Lac Hong University and Enterprises in Dong Nai Province - Dung, Tran (Social Science Learning Education Journal, 2017)
The linking between Universities and enterprises is an objective requirement based on the principles of education: Learning with practice, education combined with productive labor, education of University attached "Education of the family and society", "The University teaches the society, not the training of the University"... In Vietnam, this issue has not been seen by the subject in a way. Thorough, the link between the university and the enterprise is quite superficial, fragmented, low efficiency, resulting in a serious imbalance in supply and demand of high quality human resources. This paper was conducted during the time from June, 2014 to July, 2016. The research result showed that there were 550 enterprises who to be interviewed and answered nearly 6 questions. The researcher had analyzed KMO test, the result of KMO analysis used for correlation analysis. Enterprisesâ responses were measured through an adapted questionnaire on a 5-point Likert scale. Hard copy and online questionnaire were distributed among enterprises in Dong Nai province. The research results were processed from SPSS 20.0 software.